We have to find the value of (x^2+2x-3)/|x-1| as x approaches from the left.

As x approaches from the left x - 1 is always negative, so we have |x - 1| = (1 - x)

lim x--> 1 [ (x^2+2x-3)/(1 - x)]

lim x--> 1 [ (x^2+3x - x-3)/(1...

## Get

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to find the value of (x^2+2x-3)/|x-1| as x approaches from the left.

As x approaches from the left x - 1 is always negative, so we have |x - 1| = (1 - x)

lim x--> 1 [ (x^2+2x-3)/(1 - x)]

lim x--> 1 [ (x^2+3x - x-3)/(1 - x)]

lim x--> 1 [ (x(x + 3) - 1(x + 3)/(1 - x)]

lim x--> 1 [ (x - 1)(x + 3)/(1 - x)]

lim x--> 1 [ -(x + 3)]

substitute x = 1

=> - 4

**The required value of the limit is -4**